Associations of women’s empowerment with neonatal, infant and under-5 mortality in low- and /middle-income countries: meta-analysis of individual participant data from 59 countries - Zulfiqar A Bhutta; David T Doku; Subas Neupane (BMJ Global Health)
Background Child survival and women’s empowerment are global public health concerns and important sustainable development goals (SDGs). Low- and middle-income countries (LMICs) have the largest burden of both phenomena. The aim of this study is to investigate a measure of women’s empowerment at individual and population levels and its potential associations with neonatal, infant and under-5 mortality at national and regional levels in 59 LMICs.Methods We used pooled population-based cross-sectional surveys from 59 LMICs (n=6 12 529) conducted from 2000 to 2015 using standardised protocols. We constructed individual-level women’s empowerment index (ILWEI) and population-level women’s empowerment index (PLWEI) for LMICs and investigated the potential associations of these measures with neonatal, infant and under-5 mortality using two-stage random-effect individual participant data (IPD) meta-analysis.Results The pooled neonatal mortality rate was 24 per 1000 live births. Infant and under-5 mortality rates were 43 and 55/1000 live births, respectively. In the pooled sample, 61.6% and 19.9% of women had autonomy regarding their healthcare and household decision-making, respectively, whereas 56.0% rejected domestic violence against women for any reason. IPD meta-analysis showed that children of women with low ILWEI had a higher risk of neonatal (OR: 1.18, 95% CI 1.14 to 1.22), infant (OR: 1.12, 95% CI 1.08 to 1.17) and under-5 (OR: 1.12, 95% CI 1.07 to 1.18) mortality compared with children of high ILWEI. Similar relationships were found across most of the regions as well as between PLWEI and all the three outcomes.Conclusions Women’s empowerment at individual and population levels is associated with neonatal, infant and under-5 mortality in LMICs. Our study underscores the importance of women’s empowerment in accelerating progress towards the attainment of the SDG targets for child survival in LMICs. Multi-sectoral and concerted efforts are necessary to eliminate preventable child mortality in these countries.